ANALISIS DAMPAK REVITALISASI PASAR TERHADAP JUMLAH PELANGGAN DAN PENDAPATAN PEDAGANG DI PASAR BADUNG - Yuskarnaya, I Putu; Yuliarmi, Ni Nyoman (E-Jurnal Ekonomi Pembangunan Universitas Udayana; Vol 11 No 7 (2020): VOL 11 NO 7, JULI 2022 [2481-2899], 2022)
The center of trade is one of the links of the chain of economic activities of the community which is an effort by the government to control the physical and non-physical environment as a form of revitalization of traditional markets. The purpose of this study was to analyze the impact of market revival in the Badung market on the number of customers and traders' income, the number of samples of 94 traders, and the sampling method was pair sampling. Based on the results of the analysis and discussion we conducted, it can be concluded that although the market was revitalized, the revitalization of the market did not have a positive impact on the number of customers and the income of traders in the Badung market. After the implementation of the traditional market revitalization program, it is expected that maintenance and maintenance will continue to be carried out to increase the number of customers and the income of traders. Keywords: market revitalization, number of customers and revenue.